Fungal community response to long‐term soil warming with potential implications for soil carbon dynamics. Issue 5 (11th May 2021) - Pec, Gregory J.; van Diepen, Linda T. A.; Knorr, Melissa; Grandy, A. Stuart; Melillo, Jerry M.; DeAngelis, Kristen M.; Blanchard, Jeffrey L.; Frey, Serita D.
Abstract: The direction and magnitude of climate warming effects on ecosystem processes such as carbon cycling remain uncertain. Soil fungi are central to these processes due to their roles as decomposers of soil organic matter, as mycorrhizal symbionts, and as determinants of plant diversity. Yet despite their importance to ecosystem functioning, we lack a clear understanding of the long‐term response of soil fungal communities to warming. Toward this goal, we characterized soil fungal communities in two replicated soil warming experiments at the Harvard Forest (Petersham, Massachusetts, USA) which had experienced 5°C above ambient soil temperatures for 5 and 20 yr at the time of sampling. We assessed fungal diversity and community composition by sequencing the ITS2 region of rDNA using Illumina technology, along with soil C concentrations and chemistry. Three main findings emerged: (1) long‐, but not short‐term warming resulted in compositional shifts in the soil fungal community, particularly in the saprotrophic and unknown components of the community; (2) soil C concentrations and the total C stored in the organic horizon declined in response to both short‐ (5 yr) and long‐term (20 yr) warming; and (3) following long‐term warming, shifts in fungal guild relative abundances were associated with substantial changes in soil organic matter chemistry, particularly the relative abundance of lignin. Taken together, our results suggest that shifts with warming in the relative abundance of fungal functional groups and dominant fungal taxa are related to observed losses in total soil C.